THE IMPLEMENTATION OF PROBLEM-BASED LEARNING THROUGH WEB QUEST IN TEACHING WRITING - Puspitasari, Esti (2017)
This study investigates the implementation of problem-based learning through WebQuest in teaching writing to second graders of a Senior High School in Bekasi. It aimed at finding out the implementation of problem-based learning through WebQuest in teaching writing and the students' perceptions of the implementation of problem-based learning through WebQuest in teaching writing. The study employed descriptive qualitative research design. The data were obtained from several instruments, namely classroom observation, interview, and questionnaire. The findings showed that the teacher has implemented problem-based learning through WebQuest in teaching writing as suggested by Tan (2003), although there were different activities at some stages. In addition, during the process of implementing problem-based learning, the teacher faced some problems: choosing the problem, internet access, and time allocation. In addition, it also was found that students perceived that WebQuest was useful, easy to use. Additionally, they were motivated and enthusiastic to study. Keywords: problem-based learning, WebQuest, teaching writing;--- Penelitian ini membahas tentang implementasi problem-based learning melalui WebQuest dalam pengajaran menulis pada siswa kelas 2 di Sekolah Menengah Atas Negeri di Bekasi. Penelitian ini bertujuan untuk mengetahui bagaimana implementasi problem-based learning melalui WebQuest dalam pengajaran menulis. Penelitian ini menggunakan deskriptif kualitatif. Data dikumpulkan dengan menggunakan beberapa instrument, yaitu observasi kelas, interview dan kuesioner. Hasil penelitian menunjukan bahwa guru tersebut sudah mengimplementasi problem-based learning melalui WebQuest dalam pengajaran writing seperti yang disarankan oleh Tan (2003), meskipun dalam pengajarannya ada beberapa aktivitas yang berbeda dalam beberapa tahapan. Selain itu, dalam proses pengimplementasian problem-based learning, guru menghadapi beberapa masalah yaitu pemilihan topic, akses internet, dan alokasi waktu. Penelitian lain juga ditemukan bahwa siswa merasa WebQuest sangat berguna, dan mudah untuk di akses. Ditambah lagi, mereka merasa termotivasi dan antusias dalam belajar. Kata kunci: problem-based learning, WebQuest, pengajaran menulis